If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -11 = -67 Reorder the terms: -11 + 7x = -67 Solving -11 + 7x = -67 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 7x = -67 + 11 Combine like terms: -11 + 11 = 0 0 + 7x = -67 + 11 7x = -67 + 11 Combine like terms: -67 + 11 = -56 7x = -56 Divide each side by '7'. x = -8 Simplifying x = -8
| 5-4x=-6x+5 | | 5z^3+15z^2= | | 6y^2-12y=gcf | | 2(x-5)-4=0 | | -6(x+1)-11=32+5 | | 9-2x=x-27 | | ln(x+11)-ln(x-3)=ln(3) | | 7(5c-1)-8=33c+7 | | 2x^4-4x^3-x^2+2x=gcf | | -24=21x | | -3x+5=-31-7x | | 3x+9=10y+8 | | 5z^3+15z^2+3z+9= | | 16x+4y=7 | | -56-2x=5x+7 | | 2x+-6+-4x+9=5x | | x(x+13)=x+10(x+1) | | y/5-9=-2 | | 6=12s-6/5 | | 1=.5x-1 | | 2x-6-4x+9=5 | | w/2+14=12 | | x-1/2=5/6 | | 5y+26=y+10 | | (v^2-3v-40)/(v+3) | | 17=7-(y+8) | | 8.1x^6+6.3x^5-4.5x^2+3.6x= | | 3(x+6)+2(x-2)=6x | | 34-6x=5 | | 6+y=-44 | | (v+3)/(v^2-3v-40) | | 5y+6y=y+10 |